(untitled) (Reflection and Critique Law Magazine, 2022)
This study seeks to reflect on how critical human rights theories, decolonial studies and feminist theories can contribute in an intersectional way to analyze the demands faced by black women domestic workers in Brazil. Therefore, the objective is to focus on domestic work in the country in the light of theoretical-critical and decolonial discussions, with the main scope of understanding the conditions historically imposed on black women who exercise this profession in the country. To this end, a bibliographic review of theoretical frameworks is carried out that visit issues of race, coloniality, human rights and feminist theories as milestones for the recognition of the rights of these workers. It is concluded that the advances made in this area were not enough to break with the colonial and slave-holding characteristics involving the group.